The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ja910973a
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Palladium(II) Catalysis: C−H Activation/Suzuki−Miyaura Couplings at Room Temperature

Abstract: Cationic palladium(II) catalyst realized facile C-H activation of aryl urea with arylboronic acids at room temperature. This reaction is extremely mild to carry out aromatic C-H activations through electrophilic substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(72 citation statements)
references
References 49 publications
0
68
0
Order By: Relevance
“…Regardless of this, however, there are many examples of aqueous media reactions, [5] water used as a co-solvent or on-water [6] reactions performed without dissolving the organic compounds (coined as the "on-water-effect"). Efforts have been made to dissolve organic compounds in water by adding additives like surfactants [7] and applying heat.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of this, however, there are many examples of aqueous media reactions, [5] water used as a co-solvent or on-water [6] reactions performed without dissolving the organic compounds (coined as the "on-water-effect"). Efforts have been made to dissolve organic compounds in water by adding additives like surfactants [7] and applying heat.…”
Section: Introductionmentioning
confidence: 99%
“…When bromobenzene, which is less reactive than iodobenzene because of the larger CÀBr bond energy, is used, the TOF values of the 34-nm-sized Pd NP sample were 0.24 s À1 at 85 8C and 39.3 h À1 at room temperature. [29,30] There have been no reports with Pd nanostructures as the catalysts at room temperature. So far, the Suzuki coupling reactions at room temperature have been reported only with Pd complexes as the catalysts.…”
mentioning
confidence: 99%
“…Liu et al [54] reported the synthesis of substituted dibenzofuran by phenol- Lipshutz et al [70] reported an unusual effect of cationic Pd in Suzuki-Miyaura reaction without using any metal oxidants or acid (Scheme 42). The authors found facile C-H activation of aromatic moiety followed by cross-couplings at room temperature.…”
Section: C(sp 2 )−H Activation and Functionalizationmentioning
confidence: 99%